Behavioral intention of mobile health application adaptation with demographics and m-financial incentives payment as moderating variable (Journal of Pharmaceutical Negative Results, 2022)
Information technology has been seen to improve rapidly over the last decade. This increase was due to the increase in the number of internet users and advances in mobility technology(Aswani et al., 2018). The presence of non-banking institutions engaged in the world of digital technology has begun to reduce the dominance of conventional banking institutions that has been going on so far(Fahlevi, 2021). The growing complexity of consumer needs, the increasing cost of traditional methods and the need for innovative customer-centric solutions make it necessary to design alternative mobile-based technologies as business solutions(Kuganathan & Wikramanayake, 2014). These various things have created tremendous opportunities to innovate through online-based payment systems(Fahlevi & Alharbi, 2021). The Less Cash Society (LCS) is an effort by Bank Indonesia to increase the use of non-cash transactions.